Load Frequency Response in the Chilean Power System - Chavez-Orostica, H; Fuentes-Parra, C; Quiroz-Moreno, J (IEEE, 2022)
The current transition from synchronous to power electronics-based generation has led to important concerns in power systems operation, particularly on the reduction of natural frequency response from synchronous machines. These concerns have increased the interest in monitoring and estimating the overall frequency response of power systems, which has been centered in the response of generators that comprises most of system response. However, the load frequency response has been overlooked as its contribution is not as significant as that of generators, and also because of the large amount of individual loads within a power system that are challenging to monitor. This paper reports the load frequency response in the case of Chile, considering SCADA and Syncrophasor data. A set of representative loads is considered to evaluate the frequency response and extrapolate this behavior to assess the overall load frequency response.